PROSES BERPIKIR KRITIS SISWA KELAS XII MAN 3 JEMBER BERDASARKAN PERKEMBANGAN USIA DALAM MENYELESAIKAN SOAL MATEMATIKA POKOK BAHASAN PELUANG - Suharto, Suharto; Sapta, Hendra; Kurniati, Dian (Department of Mathematics Education , University of Jember, 2017)
Abstract. The research is descriptive research qualitative described profile aims to think critically graders xi man 3 jember in resolving math problem with difference in age students different .The subject is done with the snowball throwing up to a whole considered saturated data .From the data analysis , obtained the conclusion that students xii-ipa 1 man 3 jember from 18 years in resolving about opportunities , able to reach all indicators used the focus , reason , inference , situation , clarity and overview .At the age of this students had more pola-pola off other students , students at age it also more detail in working on a about . A student xii-ipa 1 man 3 jember from 17 years in resolving about opportunities , able to reach 5 an indicator of 6 the indicators used the reason , inference , situation , clarity and overview. Students at age it not thorough in doing this is that there is a subject not capable of wrote indicators the focus . A student xii-ipa 1 man 3 jember from 16 years in finish about opportunities , able to reach 5 an indicator of 6 the indicators used the focus , reason , situation , clarity and overview .Same as well as earlier age , students is also not thorough to work thus unable to write indicator to three categories inference . Keywords: Profile think Critically, Solve Math Problem